Antibiotic resistance of microorganisms isolated from the urine of patients before surgical treatment for benign prostatic hyperplasia: results from a 7-year single-center study - M. I. Kogan; V. L. Medvedev; Yu. L. Naboka; D. V. Sizyakin; S. N. Ivanov; G. A. Palaguta; I. A. Gudima (Вестник урологии)
Introduction. The tendency of microorganisms to develop resistance mechanisms is a widely discussed and signiﬁcant problem worldwide. Studying regional diﬀerences in the qualitative characteristics of microorganisms provides valuable information for empirically preventing and treating infectious complications, as well as providing an enhanced understanding of the variability in microbial community properties within the clinical context of diseases and patients' comorbidity status.Objective. To assess the antibiotic resistance of microorganisms isolated in high titers from the urine samples of patients with benign prostate hyperplasia (BPH) prior to surgery.Materials & Methods. This single-center, retrospective study conducted from March 2016 to February 2023 included 59 suprapubic-draining BPH-patients (Group I), 46 drainage-free BPH-patients with leukocyturia (Group II), and 44 drainage-free BPH-patients and no leukocyturia (Group III). Inclusion criteria: indications for BPH surgery, no history of sexually transmitted diseases, no symptoms of urinary tract infection, and no prostate cancer. The patient's voluntary informed consents to participate were also obtained.Results. The rates of resistance to ciproﬂoxacin in patients of Group I were statistically signiﬁcantly higher compared to Group II (85.7% vs 55.6%, p = 0.002). Resistance of gram-negative microorganisms to meropenem and imipenem was higher in Group III compared to Group I (31.1% vs 13.7%, p = 0.006 for meropenem and 44.5% vs 9.8%, p = 0.001 for imipenem, respectively). Resistance of Gram-positive microorganisms to ampicillin in Groups I to III was 13.6%,6.3% and 20.0%, respectively with no signiﬁcant diﬀerence between groups (p > 0.05). However, there was extremely high resistance among veriﬁed Gram-positive organisms to all the drugs in the ﬂuoroquinolone class (ciproﬂoxacin, norﬂoxacin, levoﬂoxacin) ranged from 63.6% to 80.0%.Conclusion. The present study demonstrates that the isolation frequency of antibiotic-resistant microorganisms from the urine sample of drainage-free BPH-patients or no clinical and laboratory signs of inﬂammation in the urinary tract is high. The presence of antibiotic resistance provides risks for developing diﬃcult-to-control infectious complications. Currently, assessment of urine-derived microbial antibiotic resistance should be considered in every BPH-patient with indications for surgical management of bladder outlet obstruction, regardless of the presence of risk factors.